Access to primary health care for acute vascular events in rural low income settings: a mixed methods study. Issue 1 (December 2017) - Ahmed, Shyfuddin; Chowdhury, Muhammad; Khan, Md.; Huq, Nafisa; Naheed, Aliya
Abstract Background Cardiovascular diseases (CVDs) are the leading cause of global mortality. Among the CVDs, acute vascular events (AVE) mainly ischemic heart diseases and stroke are the largest contributors. To achieve 25% reduction in preventable deaths from CVDs by 2025, health systems need to be equipped with extended service coverage in order to provide person-centered care. The overall goal of this proposed study is to assess access to health care in-terms of service availability, care seeking patterns and barriers to access care after AVE in rural Bangladesh. We will consider myocardial infarction (MI) and stroke as acute vascular events. Methods/Design We will conduct a mixed methods study in rural Matlab, Bangladesh. This study will comprise of a) health facility survey, b) structured questionnaire interview and c) qualitative study. We will assess service availabilities by creating an inventory of public and private health facilities. Readiness of the facilities to deliver services for AVE will be assessed through a health facility survey using 'service availability and readiness assessment' (SARA) tools of the World Health Organization (WHO). We will interview survivors of AVE and caregivers (present and accompanied the person during the event) of person who died from AVE for exploring patterns of care seeking during an AVE. For exploring barriers to access care for AVE, we will conduct in-depth interview with survivors of AVE and caregivers of the person who died from AVE. We will also conduct key informant interviews with the service providers at primary health care (PHC) facilities and government high level officials at central health administration of Bangladesh. Discussion This study will provide a comprehensive picture of access to primary health care services during acute cardiovascular events as stroke & MI in rural context of Bangladesh. It will explore available service facilities in rural area for management, utilization of services and barriers to access care during an acute emergency. This study will help to generate hypothesis, develop programs and policies for better access to care for AVE in similar rural settings considering barriers of access and improving utilization.